INKUIRI DAN PHET : KOMBINASI AMPUH UNTUK PEMBELAJARAN IPA YANG AKTIF DAN INTERAKTIF DI SMPN 15 KOTA BIMA - Anggraini, Alif Tulusiyah; Zulkarnaen, Zulkarnaen (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
ABSTRACT Through investigative activities involving active student participation, science learning in junior high school plays an important role in shaping students' understanding of natural phenomena and fostering scientific thinking skills. This makes the learning process more dynamic. It is necessary to implement a learning model that can activate student involvement, encourage the development of creative ideas, and provide valuable educational opportunities to improve the quality of the learning process. The purpose of this study was to assess how well PhET (Physics Education Technology) simulations and inquiry-based learning models work together to increase student engagement and interaction in science classes at SMPN 15 Kota Bima. The research methodology used was a quasi-experiment with a one-group pretest-posttest only control group design. Grade VIII students of SMPN 15 Kota Bima in the 2024–2025 academic year participated in this study; there were eight female participants and eight male participants. Tests, questionnaires, and observations were used to obtain data on student interactions and activities. Relevant statistical tests were then used for analysis. Based on the observation sheet, questionnaire, test and research results, it shows a positive influence of the combination of inquiry and PhET on student involvement in the science learning process that has been implemented on very good criteria, as well as its implications for increasing students' understanding of concepts and learning interests as seen from the analysis of the average N-Gain score with moderate criteria. Based on the description above, it can be concluded that inquiry and PhET can be a reference for teachers and other researchers in developing a more innovative and interesting science learning approach. ABSTRAK Melalui kegiatan investigasi yang melibatkan partisipasi aktif siswa, pembelajaran IPA di SMP berperan penting dalam membentuk pemahaman siswa terhadap fenomena alam dan menumbuhkan kemampuan berpikir ilmiah. Hal ini membuat proses pembelajaran jadi lebih dinamis. Diperlukan penerapan model pembelajaran yang dapat mengaktifkan keterlibatan siswa, mendorong pengembangan ide-ide kreatif, serta memberikan kesempatan pendidikan yang bernilai guna meningkatkan kualitas proses pembelajaran. Tujuan atas penelitian ini ialah guna menilai seberapa baik simulasi PhET (Teknologi Pendidikan Fisika) dan model pembelajaran berbasis penyelidikan bekerja sama untuk meningkatkan keterlibatan dan interaksi siswa di kelas IPA di SMPN 15 Kota Bima. Metodologi penelitian yang dipakai ialah eksperimen semu atas desain one-group pretest-posttest only control group design. Siswa kelas VIII SMPN 15 Kota Bima pada tahun ajaran 2024–2025 berpartisipasi dalam penelitian ini; terdapat delapan peserta perempuan dan delapan peserta laki-laki. Tes, kuesioner, dan observasi dipakai guna mendapatkan data tentang interaksi dan aktivitas siswa. Uji statistik yang relevan kemudian digunakan untuk analisis. Berdasarkan lembar observasi, kuesioner, tes dan hasil penelitian memperlihatkan adanya pengaruh positif penggabungan inkuiri dan PhET terhadap keterlibatan siswa dalam proses belajar IPA yang sudah dilaksanakan atas kriteria sangat baik, serta implikasinya terhadap peningkatan pemahaman konsep dan minat belajar siswa dilihat atas analisis rerata skor N- Gain dengan kriteria sedang. Berdasarkan uraian diatas, dapat disimpulkan bahwa inkuiri dan PhET dapat menjadi referensi bagi guru dan peneliti lain dalam mengembangkan pendekatan pembelajaran IPA yang lebih inovatif dan menarik.